Recent Advances in Surface-Enhanced Raman Scattering Magnetic Plasmonic Particles for Bioapplications - Kim-Hung Huynh; Eunil Hahm; Mi Suk Noh; Jong-Hwan Lee; Xuan-Hung Pham; Sang Hun Lee; Jaehi Kim; Won-Yeop Rho; Hyejin Chang; Dong Min Kim; Ahruem Baek; Dong-Eun Kim; et al. (Nanomaterials, 2021)
The surface-enhanced Raman scattering (SERS) technique, that uses magnetic plasmonic particles (MPPs), is an advanced SERS detection platform owing to the synergetic effects of the particles’ magnetic and plasmonic properties. As well as being an ultrasensitive and reliable SERS material, MPPs perform various functions, such as aiding in separation, drug delivery, and acting as a therapeutic material. This literature discusses the structure and multifunctionality of MPPs, which has enabled the novel application of MPPs to various biological fields.